2010
DOI: 10.1007/s11104-010-0360-z
|View full text |Cite
|
Sign up to set email alerts
|

Trade-offs between the short- and long-term effects of residue quality on soil C and N dynamics

Abstract: The decline of soil organic matter (SOM) and its associated fertility is one of the most important constraints to enhanced crop productivity in subSaharan Africa. Integrated soil fertility management recognizes the potential benefits of the combined use of organic residue and mineral fertilizer inputs for improved crop yield and SOM build up. However, these benefits may be controlled by residue quality. We examined the short-to long-term C and N dynamics following application of different quality residues with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
42
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 71 publications
(47 citation statements)
references
References 36 publications
(46 reference statements)
5
42
0
Order By: Relevance
“…In this study, application of SSB showed a tendency to increase the N distribution from applied IF to the plant and soil, thereby decreasing the rate of unaccounted N (SUR/SSB: 18%, INC/SSB: 19%, INC/IF: 46% in Table 6). This result implies that a combination of organic matter of a high C/ N ratio with IF has positive effects on the soil, air environment, and soil fertility, and is in agreement with previous reports on reduction of environmental N losses by crop residue and IF inputs (Gentile et al, 2009(Gentile et al, , 2011.…”
Section: Distributions Of N Derived From If Applied To the Plant-soilsupporting
confidence: 93%
See 2 more Smart Citations
“…In this study, application of SSB showed a tendency to increase the N distribution from applied IF to the plant and soil, thereby decreasing the rate of unaccounted N (SUR/SSB: 18%, INC/SSB: 19%, INC/IF: 46% in Table 6). This result implies that a combination of organic matter of a high C/ N ratio with IF has positive effects on the soil, air environment, and soil fertility, and is in agreement with previous reports on reduction of environmental N losses by crop residue and IF inputs (Gentile et al, 2009(Gentile et al, , 2011.…”
Section: Distributions Of N Derived From If Applied To the Plant-soilsupporting
confidence: 93%
“…This may be because of the N immobilization that occurred when applying SSB with a high C/N ratio, regardless of the application method (i.e., surface application or incorporation). The N supply potential to komatsuna was lower in the soil with both IF and SSB compared to that with IF alone, supporting the hypothesis suggested by Gentile et al (2011). However, the dry weight/N uptake ratio (Table 5) and dry weight of group, followed by the INC/SSB and INC/IF groups, but no significant difference was found among the 3 treatments.…”
Section: Effects Of Ssb On Komatsuna Growth Yield and N Uptakesupporting
confidence: 77%
See 1 more Smart Citation
“…Similarly, Bhogal et al (2011) found that manure was quickly stabilized and increased SOC for more than 2 yr. A major difference between wheat and legume residues or manure would be in N content. In a study comparing residues of low and high N content, Gentile et al (2010) found that they gave the same SOC result after a number of years, with or without fertilizer N additions. Furthermore, Gregorich et al (1997) concluded that fertilizer did not affect the turnover of either the free or physically protected light fraction organic matter, and the location of organic matter in the soil aggregates was a main factor in its susceptibility to decomposition.…”
mentioning
confidence: 97%
“…Efficient use of organic residues as fertilizers is therefore important, and there is a large literature on this topic [1,2]. Particularly high quality plant litter and residues that can release most of their nutrients during peak crop growth are valuable.…”
Section: Introductionmentioning
confidence: 99%